The Influence of Consumer Behavior on Brand Success: A Case Study of Panasonic Corporation - Singh, Padmalini; Rao, K.S. Srinivasa; Chong, Angela Yi Wen; Kee, Daisy Mui Hung; Jimmy, Adrianie Jinietia; Hong, Aileen Chun Yueng; Verma, Ashutosh; Pandey, Rudresh; Lim, Jia Yee; Khushboo, Kumari; PV, Ranjith (Asia Pacific Journal of Management and Education (APJME), 2021)
The objective of this study is to investigate the influence of consumer behavior on brand success. Consumer behavior is a study of consumers and their methods to choose, consume, and dispose of products and services, including their social, cognitive, and developmental progress. Panasonic Corporation may face the issues of consumer behavior which affects customer satisfaction and loyalty affecting the company’s development. This paper presents the factors of consumer behavior that may bring Panasonic to its success. The findings provide particular qualities to enhance the opportunity of increasing its customer satisfaction and guidance for potential development.